The foreign Debt Problem in Africa - Decoodt, Patrick (Afrika Focus, 1987)
The foreign debt problem of Sub-Saharan Africa (SSA), although an important obstacle against economic growth, is not the region’s major economic problem. The creditors are less concerned about the relative small debt figures of SSA because of the lower risks for the equilibrium of the financial system. But from the debtors’ viewpoint, the debt situation is possibly even more critical in low-income Africa than in the richer major debtor countries. SSA has a predominance of official creditors with the best obtainable credit terms. Notwithstanding these good terms, SSA is so poor that it has difficulties with fulfilling its debt service. There is no single solution for the African debt crisis. Anyway the official creditors have to adopt a more flexible attitude. The debtor countries have also to accept their own responsibility in the solutions of the problem. KEYWORDS: foreign debt problem, Sub-Saharan Africa